2023
DOI: 10.3390/molecules28041722
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Catalysis of Tea Polyphenols by Polyphenol Oxidase

Abstract: Tea polyphenol (TPs) oxidation caused by polyphenol oxidase (PPO) in manufacturing is responsible for the sensory characteristics and health function of fermented tea, therefore, this subject is rich in scientific and commercial interests. In this work, an in vitro catalysis of TPs in liquid nitrogen grinding of sun-dried green tea leaves by PPO was developed, and the changes in metabolites were analyzed by metabolomics. A total of 441 metabolites were identified in the catalyzed tea powder and control check s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Dong et al (2016) also found oxidation condensation reactions of catechin, epicatechin, and CQA were more likely to occur at higher temperatures, and the reaction rate of these three phenols was higher at 90 • C than that at 50 • C. Flavanol degradation at 40 • C was the highest, as high temperature promoted oxidation, epimerization, hydrolysis, and/or polymerization of flavanols (Ferreyra et al, 2023). Temperature dependence of reaction rates between 4-methylbenzoquinone and amino acid residues lysine followed the Arrhenius law at 15-45 • C (Liu, Poojary, et al, 2023;Liu, Chen, et al, 2023). The effects of temperature on o-quinones are quite complex.…”
Section: Temperaturementioning
confidence: 98%
See 1 more Smart Citation
“…Dong et al (2016) also found oxidation condensation reactions of catechin, epicatechin, and CQA were more likely to occur at higher temperatures, and the reaction rate of these three phenols was higher at 90 • C than that at 50 • C. Flavanol degradation at 40 • C was the highest, as high temperature promoted oxidation, epimerization, hydrolysis, and/or polymerization of flavanols (Ferreyra et al, 2023). Temperature dependence of reaction rates between 4-methylbenzoquinone and amino acid residues lysine followed the Arrhenius law at 15-45 • C (Liu, Poojary, et al, 2023;Liu, Chen, et al, 2023). The effects of temperature on o-quinones are quite complex.…”
Section: Temperaturementioning
confidence: 98%
“…(2022) also reported that CQA is the preferential substrate for PPO in apple juices. During the production of black tea, PPO mainly catalyzes catechin oxidation to generate complex products, such as theaflavins and thearubigins (Engelhardt, 2020; Liu, Chen, et al., 2023).…”
Section: O‐quinone Generation Mechanismsmentioning
confidence: 99%
“…A notable application of BD simulations can be seen in the work of Luo et al., [49] who employed dissipative particle dynamics (DPD), a variant of BD simulations, to investigate the self‐assembly of amphiphilic diblock copolymers in the presence of cosolvents. Their findings underscored how cosolvent properties, such as water affinity and composition, critically dictate the morphology and pathway of vesicle formation, thereby illustrating the pivotal role of cosolvents in polymer system self‐assembly.…”
Section: Theoretical Approaches To Understanding Intermediate States ...mentioning
confidence: 99%
“…MISA software (Liu et al, 2023a; https://webblast.ipk-gatersleben. de/misa/) was used to identify SSR loci within the A. cristatus transcriptome (Figure 1D).…”
Section: Screening Of Est-ssr Loci Screening and Primer Design Of A C...mentioning
confidence: 99%